Pembangkitan Plasma Menggunakan Metode High-Voltage Direct Current Untuk Aplikasi Direct Current Magnetron Sputtering - Syarifah Nihlah Yahya; Fadli Robiandi; Ikal Maknun (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Direct Current (DC) magnetron sputtering is one of the Physical Vapour Deposition (PVD) technique that use plasma as a medium. In this experiment, vacuum pumps, vacuum tubes (plasma reactor), capacitor, MOT transformers, HV bridge diodes, and regulator transformers is the main instrumen of DC magnetron sputtering. By ionizing the trapped gas inside the vacuum tube we created the plasma. The ionization process can be done by giving DC high voltage electricity to the trapped gas in the plasma reactor that formed plasma. DC high voltage electricity (at 800-1600 Volt) can be form using regulator transformers, MOT transformers, HV bridge diodes, and HV capacitor. Plasma’s are ignited with the distance between the electrodes which is 2, 4, 6, and 8 cm and two different vacuum pump. From the experiment we got plasma at 35 Volt on regulator transformers or 464 Volt that measure on the electrodes.